Respuesta :
*eq1 by 2 and eq2 by -3
4x+6y=12
-15x-6y=-12
-11x=0
x=0
so
3y=6
y=2
so option 3 is correct
11y=22
4x+6y=12
-15x-6y=-12
-11x=0
x=0
so
3y=6
y=2
so option 3 is correct
11y=22
Answer:
Option c :11y = 22
Step-by-step explanation:
Given :
[tex]2x+3y = 6[/tex] --(a)
[tex]5x+2y = 4[/tex] ---(b)
Solution :
First multiply equation (a) by 5 then it become :
[tex]10x+15y = 30[/tex] --(c)
Then multiply equation (b) by 2 then it becomes :
[tex]10x+4y = 8[/tex] --(d)
Now subtract (d) from (c)
⇒[tex]10x+15y -30 -(10x+4y -8)=0[/tex]
⇒[tex]10x+15y -30 -10x-4y +8=0[/tex]
⇒[tex]11y-22=0[/tex]
⇒[tex]11y=22[/tex]
Thus , option C is right.